Il faticoso cammino del PD e della sinistra nel nuovo millennio - Luciano M. Fasano; Paolo Natale (QOE-IJES)
In this article we take into consideration the difficult path of the Left in the attempt to overcome the ancient paradigm of identity, intrinsically linked to classical communism. We will retrace the electoral history and the consensus for Left and Centre-left parties from the post-war period to the present. We will analyse the transition from “voto di appartenenza” to the current situation of intense electoral volatility. An empirical analysis of the answers provided by the delegates of the Democratic Party from 2007 to 2013 shows how the heirs of the Communist Party have undergone a constant process of fragmentation, both within the camp and within the parties themselves, The work closes with an attempt to understand (and predict) what the future of the difficult path of the Left within the epochal changes of Western society might be.